Patrioitic Note in Sarojini Naidu’s Poetry - Chouhan, Sandhya (Journal of Advanced Research in English & Education; Vol 5 No 2 (2020): Journal of Advanced Research in English and Education, 2021)
Sarojini lived and created in those stirring times when India was passing though the stages of her struggle for freedom. It was the age of such great patriots and freedom-fighters as Gandhi, Nehru, Gokhale, Tilak and many others and she had close contacts with all these heroic personalities. Patriotism was in the air so to say, and Sarojini could not remain unaffected by the spirit of the times. After her meeting with Gandhi in 1914, she herself plunged into the thick of the bottle, and her letters and speeches are full of her deeply felt love for her motherland. This love is also reflected at every step in her poetry. India was is her blood; it was as part and parcel of herself, and the note of patriotism is struck in numerous poems written at different periods. It is expressed in her poems, ‘To India’, ‘The Gift of India’, ‘An Anthem of Love’, ‘Lokman Tilak’, etc. How to cite this article:  Chouhan S. Patrioitic Note in Sarojini Naidu’s Poetry. J Adv Res Eng & Edu 2020; 5(2): 8-10. DOI: https://doi.org/10.24321/2456.4370.202006